Regiochemical and Stereochemical Studies of the Intramolecular Dipolar Cycloaddition of Nitrones Derived from Quaternary Aldehydes - Alkayar, Ziad T. I.; Adams, Harry; Coldham, Iain (Synlett, 2016)
Three aldehydes each with a quaternary α-carbon stereocentre bearing an alkenyl, a phenyl, and a methyl ester group were treated with N-methylhydroxylamine. In each case bicyclic isoxazolidine products were formed by condensation to give intermediate nitrones that undergo intramolecular dipolar cycloaddition. The stereoselectivity was influenced by the α-carbonyl substituent, possibly by a hydrogen bond between CO and a nearby CH of the nitrone in the transition state (supported by DFT and X-ray studies), and the regioselectivity was affected by the length of the tether and by the presence of an ester on the alkene dipolarophile.
Keywords: cycloaddition; diastereoselectivity; domino reaction; fused-ring systems; heterocycles